The Influence Of Social Media On Sexual Knowledge And Behavior Of Adolescents In Gorontalo City - Maimun Ihsan; Elvie Febriani Dungga; Gefira Nur Fatimah Sailama (Jambura Nursing Journal, 2023)
The freedom of adolescents in establishing relationships through social media can also trigger sexual behavior. This study aims to determine the effect of social media on knowledge and sexual behavior in adolescents in Gorontalo City. The population in this study is the entire sample. The sampling technique in this study used a simple random sampling technique. This research was conducted by means of an analytic study with a cross-sectional research design by studying the correlation between the influence of social media (independent) with knowledge and sexual behavior (dependent). The results of the alternative statistical test Chi-Squere test between social media and sexual knowledge obtained a p value of 0.532. The results of the alternative statistical test Chi-Squere test between social media and sexual knowledge obtained a p value of 0.000 which is smaller than the significance value (p), which is 0.05 (p